Impact of provision of optimum diabetes care on the safety of fasting in Ramadan in adult and adolescent patients with type 1 diabetes mellitus. (November 2020) - Alawadi, Fatheya; Alsaeed, Maryam; Bachet, Fawzi; Bashier, Alaaeldin; Abdulla, Khadija; Abuelkheir, Sona; Rashid, Fauzia; Abdulaziz Bin Hussain, Azza; Abdelgadir, Elamin; Alsayyah, Fatima; Elsayed, Mohamed; Hassanein, Mohamed
Abstract: Background: All diabetes and Ramadan guidelines advice against fasting for people with type 1 diabetes, however, many insist on fasting. Consequently, this causes a challenge due to the risk of hypoglycaemia, hyperglycemia ± diabetic ketoacidosis. Aim: To assess the impact of optimum care, which includes Ramadan-focused education, flash glucose monitoring, dietary advice and treatment adjustment on the safety of Ramadan fasting in people with type 1 diabetes. Methods: Thirty persons with type 1 diabetes who insisted to fast during Ramadan were recruited to the study. At pre-Ramadan visit, all patients received Ramadan focused education and Freestyle Libre (FSL) sensor insertion and training. Patients used the sensor for 6 weeks (pre-Ramadan and during Ramadan). The physical and biological parameters were collected 2–4 weeks before and after Ramadan. Results: 22 patients on basal bolus insulin and 2 on an insulin pump had FSL data. Average number of days fasted were 24. Learning benefits was reported by 95% of patients following pre-Ramadan educational session. There was no clinically significant change in physical and/or biological data between pre and post-Ramadan. 63% reported making insulin dose adjustments in Ramadan. Flash glucose monitoring data showed 46.7% of patients had more than 10 hypoglycemic episodes in the 2 weeks prior to Ramadan compared to 29.2% during Ramadan . However, none of the data were statistically significant apart from HbA1c which reduced from prior to RamadanHbA1c of 8.2% to 7.9% post Ramadan (P 0.010). There was one DKA on 2nd day of Ramadan, reported due to missing insulin dose to avoid hypoglycemia. Conclusion: Optimal care of selective patients with type 1 diabetes with a low complication rate may allow Ramadan fasting with improvement in glycemic control and without an increase in hypoglycemia, biometric or metabolic parameters. Larger, randomized controlled trials are required to be able to generalize this as a recommendation.